Study on the threshold value of disaster-causing factors of engineering slope cutting in red-layer areas - Pan, Yuangui; Chen, Kezhu; Gao, Meiben; Wu, Zhonggeng; Zheng, Guoqiang; He, Qingqing; Lu, Feng; Wan, Yi; Du, Chunyang; Cao, Nan; Xie, Xiaoguo (Frontiers in Earth Science, 2022)
The phenomenon of slope cutting in engineering construction to obtain larger floor area is increasing. Slope cutting destroys the natural stability of slopes and leads to slope instability and sliding. In order to solve the problem of geological disasters caused by artificial slope cutting, Cangxi County is used as an example to analyze the slope cutting slope and height of different slope structures in the county, to study the disaster mode and disaster factors caused by slope cutting, and to analyze the influence of slope cutting height and slope cutting slope on the disaster process. The study shows that: the stability of slope cutting on different types of slopes is weakened to different degrees, with mixed rocky-soil slopes having the strongest resistance to weakening, thick-soil slopes the second strongest, and thin-soil slopes the worst; slope cutting is the main factor of disaster, and rainwater infiltration promotes landslide formation; numerical simulation is used to determine the proximity of slope cutting height and proximity of slope cutting slope, and 75% of the critical value is taken as the proposed threshold value of slope cutting. The proposed threshold value matches with the actual stable cut slope height and cut slope gradient on site, and the research results can provide reference for the decision of engineering cut slope in Cangxi County and similar red layer areas.